2017
DOI: 10.1016/j.ijid.2017.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of invasive pneumococcal and Haemophilus influenzae diseases in Northwestern Ontario, Canada, 2010–2015

Abstract: In Northwestern Ontario, the incidence of invasive Hia disease exceeds that of H. influenzae type b (Hib) in the pre-Hib vaccine era. This provides strong support for the development of a new Hia vaccine. Improved pneumococcal vaccination of high-risk adults in the region is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 36 publications
5
22
1
Order By: Relevance
“…Disease prevalence of other encapsulated strains is 24 also increasing at an alarming rate and Hia disease burden now exceeds that of Hib during the pre- 25 Hib vaccination era in some regions and populations [15]. A recent report of particular interest 26 found that Hia constituted 50% of all H. influenzae cases between 2010 and 2015 in Northwestern 27 Ontario, Canada [16]. Importantly Hib also remains an issue in countries that have not implemented 28 a vaccination program [17].…”
Section: Introductionmentioning
confidence: 99%
“…Disease prevalence of other encapsulated strains is 24 also increasing at an alarming rate and Hia disease burden now exceeds that of Hib during the pre- 25 Hib vaccination era in some regions and populations [15]. A recent report of particular interest 26 found that Hia constituted 50% of all H. influenzae cases between 2010 and 2015 in Northwestern 27 Ontario, Canada [16]. Importantly Hib also remains an issue in countries that have not implemented 28 a vaccination program [17].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence rate of an invading disease adjusted to a population of 100,000 was suggested in the literature [6][7][8][9][10]. As of April 12, 2020, none were found incorporating CFR with both CFR100 and total con rmed cases(TCC) on a population of 100,000(here we name CFR100 and TCC100, respectively) in a study.…”
Section: Introductionmentioning
confidence: 89%
“…Numerous documents have reported using CFRs to compare death tolls of speci c diseases [5]. The incidence rates and CFRs adjusted by a population of 100,000 can be reasonably compared with one other [6][7][8][9][10]. We made an effort to combine both CFR(or CFT100) and TCC100 on a dashboard, which is novel, innovative, and rarely seen in past literature.…”
Section: What This Nding Adds To What We Already Knewmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 5,054 articles by searching the keywords "case fatality rate" on PubMed Central (PMC) [11]. The use of incidence per 100,000 population to describe a disease has been suggested in the literature [12][13][14][15][16]. Countries most struck by the COVID-19 based on the infectious density can be identified in this way.…”
Section: Comparisons Of Confirmed Cases Different On a Population Of mentioning
confidence: 99%